Study of Patients with Diabetic Ketoacidosis Admitted at the Pediatric Emergency Service at Childrens Hospital Dr. Jeser Amarante Faria (Global Journal of Medical Research, 2023)
A retrospective study based on the review of medical records in the Tasy system of patients admitted with diabetic ketoacidosis in the emergency service at Children's Hospital Dr. Jeser Amarante Faria, Joinville-SC. 88 medical records were analyzed, corresponding to 71 patients, nine patients with more than one hospitalization, a majority of females (78%), age range from 1.3 to 17.1 years. A mean of five days of hospitalization, with 21 cases requiring hospitalization in the intensive care unit was noted, along with severe diabetic ketoacidosis in 59 consultations. Patients who never had a diabetic decompensation were 44% of the consultations. Hypoglycemia was the most common complication (24%), and no deaths were recorded during the evaluated period. Girls with a mean age of 10 years were the main group admitted with diabetic ketoacidosis, and this medical emergency is still often the first manifestation of type 1 diabetes mellitus in our midst.
Keywords: diabetes mellitus type1 ∙ diabetic ketoacidosis ∙ pediatrics